Prevalence and associated factors of anxiety disorder symptoms among people with epilepsy in Mekelle, Ethiopia, 2019: Institutional‐based cross‐sectional study - Jemal Seid; Kalayu Mebrahtu; Fantahun Andualem (Wiley, 2022)
Abstract Aim Anxiety can have a profound influence on the health‐related quality of life of people with epilepsy and caregivers. The study aimed to assess the prevalence and associated factors of anxiety disorder among people with epilepsy. Design An institutional‐based cross‐sectional study was conducted. Method From 18 April 2019-30 May 2019, systematically selected 300 peoples with epilepsy were recruited. Anxiety was assessed by using the generalized anxiety disorder‐7 (GAD‐7). The data were entered by using Epi Info and analysed by SPSS version 25. Result The prevalence of anxiety was 38.3%. Secondary educational status, medication‐related side effect, substance use history, seizure‐related physical trauma, stress symptoms and a mental illness belief were significantly associated factors. The prevalence of anxiety disorder symptom was high, and it reinforced the need for recognition and treatment of mental disorders in people with epilepsy.